Matrices de contabilidad social para las regiones de México - Joana Cecilia Chapa Cantú; Marco Mosqueda Chávez; Erick Rangel González (Banco de México, 2019)
– Social Accounting Matrixes are built from the four regions of the country (north, north center, center and south). In addition, it is also presented the model of accounting multipliers to identify structural differences of the regions, and the analyses of redistributive effects (sectoral recomposition) involving interdependence among institutions when exogenous income injections are given to households, which are endogenously derived by changes in relative income shares. The main results suggest the existence of significant regional differences in income-spending patterns. The southern region is characterized by the largest expansion in income when their households and self-employed workers receive an exogenous injection of income. Similarly, it is in the southern region where the highest redistributive income is observed; followed by the northern and the central regions.
Keywords: D57; D58; D3; 330; Social Accounting Matrix; Diffusion Effects; Absorption Effects; Accounting Multipliers Model